2000
DOI: 10.1034/j.1399-0039.2000.560302.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis suggests susceptibility genes for deficiencies of IgA and several other immunoglobulins on the [HLA‐B8, SC01, DR3] conserved extended haplotype

Abstract: The extended major histocompatibility complex (MHC) haplotype [HLA-B8, SC01, DR3] is increased in frequency among patients with immunoglobulin (Ig)A deficiency and common variable immunodeficiency. Because the genomic region from HLA-B to HLA-DR/DQ is virtually the same on all instances of the haplotype in the general population, we reasoned that all independent instances of [HLA-B8, SC01, DR3] carry MHC susceptibility genes for these disorders. To define immunoglobulin deficiencies determined by genes on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
1
27
0
1
Order By: Relevance
“…We had earlier explored the nature and extent of apparent penetrance of Igds through the study of unrelated individuals who were homozygous, heterozygous or non-carrying for CEHs [5][6][7] known or suspected to carry susceptibility genes for MHC-determined Igds such as IgAd [16], IgDd [22], IgG3d and IgG4d. CEHs are ≥ 1 Mb stretches of fixed genomic DNA defined by their HLA-B, complotype, and HLA-DR alleles [23].…”
Section: Why Would Two Supposedly Genetically Identical Individuals Dmentioning
confidence: 99%
See 2 more Smart Citations
“…We had earlier explored the nature and extent of apparent penetrance of Igds through the study of unrelated individuals who were homozygous, heterozygous or non-carrying for CEHs [5][6][7] known or suspected to carry susceptibility genes for MHC-determined Igds such as IgAd [16], IgDd [22], IgG3d and IgG4d. CEHs are ≥ 1 Mb stretches of fixed genomic DNA defined by their HLA-B, complotype, and HLA-DR alleles [23].…”
Section: Why Would Two Supposedly Genetically Identical Individuals Dmentioning
confidence: 99%
“…It is elevated in frequency in patients with a variety of autoimmune diseases, including T1D [24], GSE [26], myasthenia gravis [27] and systemic lupus erythematosus [28]. It is also associated with IgAd [16], IgDd [22], IgG3d [5] and IgG4d [5].…”
Section: Why Would Two Supposedly Genetically Identical Individuals Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, despite the development of high-density genetic maps and large kindred studies, the point has not been completely settled; although the telomeric part of the MHC class III region is usually favored (13,15), a report points to the telomeric part of the MHC class II region (19). Most studies published in recent years (13,14,19,20) have focused on IgAD patients bearing the B8-DR3 haplotype, because this is the most common haplotype associated with IgAD in Caucasians. However, in Spanish white IgAD patients, HLA-DR1 and HLA-DR7 are even more frequent than HLA-DR3 (21), reflecting the distribution of HLA-DR alleles and extended haplotypes in southern Europe, where HLA-DRB1*0102 (carried on the B14-DR1 haplotype) and DR7 are more frequent than in northern Europe and the U.S. (22).…”
mentioning
confidence: 99%
“…Although for each individual genotype, 95% confidence interval was very large and no statistically significant results could be obtained, the data were rather impressive and added to that of their sum shown in the previous paragraph (P ¼ 0.00001; OR ¼ 3.94) point to a dose-related effect in most instances. It has been recently reported, 17 studying individuals positive for the HLA-DR3/B8 haplotype, that increased frequencies of IgAD are only found in homozygotes for this conserved, extended haplotype and have suggested a recessive inheritance with a low penetrance. Although we have observed that all three susceptibility MHC haplotypes (those carrying either DRB1 * 0102, DR7, or DR3-TNFa2b3) are sufficient for conferring susceptibility to IgAD, we also see that they are greatly influenced by genes on the other MHC haplotype, and the strong dosage effect of the HLA-DR3/B8 haplotype has to be acknowledged.…”
mentioning
confidence: 99%